57‐2: Distinguished Paper: Laser‐Addressed Full‐Color Photo‐Quality Rewritable Sheets Based on Thermochromic Systems with Leuco Dyes. Issue 1 (29th May 2019) - Kaino, Yuriko; Kurihara, Kenichi; Shuto, Aya; Mizuno, Hiroshi; Asaoka, Satoko; Ishida, Takehisa; Takagi, Kenji; Takahashi, Isao; Amago, Hirohisa; Takeuchi, Taichi; Tejima, Asuka; Watanabe, Maho; et al.
Abstract : We have developed a laser‐addressed full‐color rewritable sheet based on a thermochromic system with leuco dyes. It achieved photographic quality images with a high resolution of 426 ppi and wide color gamut. Non‐contact laser writing on a free‐form sheets will create applications with on‐demand rewritable image design on various surfaces.